Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages a larger section of industrial workers, including mining, engineering, paint, and food manufacturers, etc. The Trades Union Congress is negotiating further awards for particular types of workers. In addition, a Factory Inspector has the power to grant a certificate for the issue of protective clothing necessary to health and safety, such as rubber aprons or special boots. So if you think workers in your factory require protective clothing for which they must give up coupons, you should take the matter up (a) with the Factory Inspector to grant a certificate, (b) with your trade union who may be negotiating extra coupons for your trade. The fact that ordinary industrial overalls still require coupons has meant that "in engineering shops up and down the country women ... are working at machines and benches in their everyday clothes, with loose sleeves, belts and cardigans flapping — an invitation to accidents" (Industrial Welfare, February 1942). It is important to see that the extra clothing coupons now allowed to certain classes of industrial workers are used to remedy this, so that overalls are worn, kept in good repair and replaced as necessary, and that all workers who need the extra coupons are covered by the scheme. To reduce the provision of protective clothing in industry today would not be economizing but actually hindering production. Transport Bad transport to and from work is stated by the Select Committee on National Expenditure (21st Report, 1940-1) to be the biggest single reason for absenteeism and loss of output. Now that factories have been dispersed to avoid bombing, it is the rule rather than the exception for workers to have long journeys to work, often of 20 or 30 miles; many of them often have to wait an hour or more to get on a bus, and then stand for the whole journey. At one large filling factory it was found that women working a ten-hour shift were away from home 14 or 15 hours. Such transport conditions must cause serious fatigue and nervous strain among the workers, and lead to a high rate of sickness and a lowering of energy for productive work. The provision of proper transport facilities is not required in the Factories Act, but under the Essential Work Order adequate transport must be provided for the workers at any scheduled firm. The management and the Regional Welfare Officer of the Ministry of Labour must be made to face up to their responsibilities in this matter. Trades councils in many places are taking up this question. Trade union organizations should take their complaints 13 21/2049